The Naming System of Ngadha Houses and the Mysteries of the Trinity in Flores, Indonesia - Watu Yohanes Vianey (Heritage of Nusantara: International Journal of Religious Literature and Heritage, 2024)
This study focuses on the sa’o ngaza, or named houses, within the Ngadha heritage in Flores, Indonesia. These named houses are categorized into three types: the source house (sa’o pu’u), derived houses (sa’o dhoro) and the tip house (sa’o lobo). The central research question explores whether the inherited names of these traditional houses carry religious significance. The study employed a qualitative descriptive approach, guiding the methods of data collection, analysis and presentation. Through the lens of cultural studies, underpinned by process philosophy and process theology, a semiotic analysis of the names ‘source house’ (sa’o pu’u), derived houses for the descendants (sa’o dhoro) and the tip house (sa’o lobo) reveals meanings and values imbued with religious concepts. These concepts, related to the nature of God in local traditions, are manifested as ‘The Beginning’, ‘The End’, and ‘The Descending to be Involved’. These are referred to as the triadic beautiful names of God, or Dewa Saga Telu. The findings of this research present Dewa Saga Telu as a semina verbi of the mysteries of the Triune God (Trinity) in accordance with local traditions. Concurrently, the findings reveal the nature of one God (Dewa Sengata), who eternally exists as three distinct persons: God Beyond (Dewa Wawo), God with us (Dewa Sa’o), and God within us (Dewa Ja’o). These findings can be interpreted as a praeparatio evangelica about the mysteries of the Trinity, fostering an intercultural dialogue between Catholic doctrine and the local cultural heritage among the Ngadha people of Flores, Indonesia.